2006
DOI: 10.1152/japplphysiol.01433.2005
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 72 overexpression protects against hyperthermia, circulatory shock, and cerebral ischemia during heatstroke

Abstract: This study extends our earlier studies in rats by applying our heatstroke model to a new species. Additionally, transgenic mice are used to examine the role of heat shock protein (HSP) 72 in experimental heatstroke. Transgenic mice that were heterozygous for a porcine HSP70i gene ([+]HSP72), transgene-negative littermate controls ([-]HSP72), and normal Institute of Cancer Research strain mice (ICR) under pentobarbital sodium anesthesia were subjected to heat stress (40 degrees C) to induce heatstroke. In [-]HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 63 publications
5
37
0
2
Order By: Relevance
“…Transcriptionally active HSF increases the expression of HSPs that promote the refolding of misfolded proteins (Li et al, 2011). Overexpression of HSPs protects against hyperthermia during heat stress (Lee et al, 2006). The rise in the concentration of HSF and HSPs could serve as a rapid protective mechanism against heat stress to maintain the homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptionally active HSF increases the expression of HSPs that promote the refolding of misfolded proteins (Li et al, 2011). Overexpression of HSPs protects against hyperthermia during heat stress (Lee et al, 2006). The rise in the concentration of HSF and HSPs could serve as a rapid protective mechanism against heat stress to maintain the homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish this at the genomic level, the genes associated with acclimation, adaptation and thermotolerance need to be identified and studied. The central role that Hsp have in cytoprotection during heat stress is shown by the fact that Hsp overexpression protects against hyperthermia and cerebral ischemia during the heat stroke (Lee et al, 2006). Heat shock (418C) causes increased Hsp synthesis, decreased protein synthesis, mitochondrial swelling and movement of organelles away from the plasma membrane associated with cytoskeletal reorganization (Edwards and Hansen, 1996;Edwards et al, 1997;Rivera et al, 2003).…”
Section: Hsp70 Genotype and Heat Stressmentioning
confidence: 99%
“…Early studies had revealed that a genetic network of heat shock transcription factors is responsible for various responses to HS (Pirkkala et al 2001;Page et al 2006). In addition, the central role of heat shock proteins (HSPs) has been described as protecting hyperthermia, circulatory shock, and cerebral ischemia during heat stroke (Lee et al 2006). Gene expression profiling of blood provides an opportunity to clarify the response of the animal to heat stress on a global level, and moreover, it will result in identification of target genes that accurately reflects not only the physiological state of the animal but also the response of the animal through the activation of various cellular processes involving various cell types.…”
Section: Introductionmentioning
confidence: 99%